Digital Communication Strategy In Improving The Image Of PT Tibeka Logistic Indonesia In Jakarta - Utami, Suci; Yulianto, Yulianto; Astuti, Marhananis Tri; Utami, Renisya Ayu (Jurnal Mamangan, 2023)
In today's modern era, Digital Communication has become an essential aspect of any organization or company. Beyond being a demand, the digital communication function at PT Tibeka Logistik Indonesia in Jakarta is crucial for enhancing the company's image and its digital communication efforts. This research aims to identify the Digital Communication Strategy in Improving the Image at PT Tibeka Logistik Indonesia in Jakarta, along with its obstacles and solutions. This study employs qualitative research methods with a descriptive approach and data collection techniques including interviews, documentation, and literature review. The findings of this study indicate that the Digital Communication Strategy in Improving the Image at PT Tibeka Logistik Indonesia in Jakarta is to build a strong network and consistently convey the company's values and mission through various digital platforms. PT Tibeka Logistik Indonesia in Jakarta's digital communication strategy emphasizes having a deep understanding of the target audience and crafting messages that are relevant to the company's values and perceptions. Communication should be carried out through the right channels, whether through the company website, social media, email, or other communication tools that match the habits and preferences of the audience. A well-directed communication strategy is key to improving the image of PT Tibeka Logistik Indonesia in Jakarta.